Kemampuan Fission Teripang Holothuria edulis dan Holothuria leucospilota (Holothuridae) Ukuran Yang Berbeda Di Kepulauan Karimunjawa - Karim, Rafsanjani A.; Hartati, Retno; Widianingsih, Widianingsih (977-2407769)
Sea cucumber is one of the important natural resources of Karimunjawa Islands. Because it has a high economic value, so fishermen exploit excessively it may reduce the population. Naturally sea cucumbers are able to reproduce asexually by fission process (division). This study aimed to determine the ability of fission and regeneration of sea cucumber Holothuria edulis and Holothuria leucospilota having different body sizes. The research was conducted in October-December 2011, in Karimunjawa waters. Jepara. Stimulation of fission carried out by binding sea cucumbers with a rubber band at 1/3 position of the anterior part. The results showed that the sea cucumber H. edulis and H. leucospilota successfully split at the 24. The difference in the size of cucumbers affect the fission time, while the intensity of regeneration of bigger sea cucumbers has higher value than a small one. The rate of fission of H. edulis and H. leucospilota 95-100%. Regeneration intensity of bigger H. edulis and H. leucospilota are higher than the small size. Posterior part of the body has higher survival rate is than the anterior.